Efficacy and toxicity of weekly paclitaxel, carboplatin, and cetuximab as induction chemotherapy or in cases of metastases or relapse for head and neck cancer with a focus on elderly or frail patients. Issue 8 (30th April 2022) - Forman, Rebecca; Deshpande, Hari; Burtness, Barbara; Bhatia, Aarti K.
Abstract: Background: Paclitaxel, carboplatin, and cetuximab (PCC) has shown promise as induction chemotherapy and in patients with metastatic/recurrent head and neck cancer (HNC). Given its tolerability, the regimen is used in frail and elderly patients. Methods: Software generated the cohort of adult patients with HNC treated with PCC in 2014–2019. Modified RECIST response rate (RR), progression‐free survival (PFS), and overall survival (OS) were calculated for the metastatic/recurrent group, and successful induction rate and RR for the induction group. These were also calculated in the elderly/frail subset (EF): age ≥75, performance status ≥2, albumin <3.5. Results: Fifty‐two percent of patients experienced ≥grade 3 toxicities. For metastatic/recurrent disease ( N  = 58), RR was 22%, mean PFS was 7.1 months. Mean OS was 15.2 months. In the induction cohort ( N  = 22), 86% reached their endpoint. The RR was 64%. There were no significant differences for EF. Conclusions: PCC is well‐tolerated with good induction success rate and reasonable PFS/OS in metastatic/recurrent disease.